KEJAHATAN KEKERASAN SEKSUAL (PERKOSAAN) TERHADAP ANAK DAMPAK DAN PENANGANANNYA DI WILAYAH HUKUM KABUPATEN CIANJUR (Universitas Suryakancana, 2016)
The rise of news about the sexual abuse of children is enough to make people shocked . This is due to most of the children who are victims of sexual violence are reluctant to report . Sexual abuse of children will go a long way in addition to result in health problems later in life is also associated with the trauma of prolonged even into adulthood . If not dealt with serious sexual abuse of children can cause social impact in the community . In providing protection for children need their systems approach that includes social welfare system for children and families, the judicial system in accordance with international standards and mechanisms to encourage appropriate behavior in society. Keywords: Sexual Abuse , Child , Impact , Handling.